Decolonising the mind the politics of language in African literature - Ngũgĩ wa Thiongʾo (London Heinemann, 1986)
Ngugi describes this book as 'a summary of some of the issues in which I have been passionately involved for the last twenty years of my practice in fiction, theatre, criticism and in teaching of literature.'
Includes bibliographies and index.
Keywords: African literature--History and criticism